Effect of Endurance Training on miR-196a and miR-133a Expression in Subcutaneous White Adipose Tissue of Wistar Rats - Saeed Daneshyar; Mohammad Reza Kordi; Mehdi Kadivar; Samane Afshari (Shahid Beheshti University, 2019)
Purpose: The aim of current study was to investigate the effect of endurance training on expression of miR-196a and miR-133a in subcutaneous white adipose tissue (WAT). Methods: 16 wistar rats were divided into two groups included: 1) Control (n=8) and 2) Endurance Training (n=8). The subjects of training group underwent continues endurance training on treadmill for eight weeks. To measure of gene expression were used the Real Time (RT) -PCR method. Results: Data showed that gene expression of UCP1 was significantly higher in trained group than control (P0.05). Conclusions: The results of this study showed that the endurance training did not change the expression of miR-196a and miR-133a in subcutaneous WAT, indicating that the endurance training-induced the increase of UCP1 expression did not relate to change of miR-196a and miR-133a expression.